Standardization of Islamic elements and requirements for room in tourism accommodation premises - Saffinee, Siti Syahirah; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim; Jamaludin, Mohd Aizat; Ahmad Fadzillah, Nurrulhidayah; Othman, Rashidi (2016)
The Muslim Friendly Hotel has been discussed since 1982 and one of the prior parts is to provide comfortable and affordable rooms to guests especially Muslim tourist. It’s related to the hospitality in Islam, which give good services to the guest in term of place to stay. However, even though in Malaysia there are nearly 3000 hotels that contribute to almost 200,000 rooms, only less than 10% are considered Islamic rooms. Consequently, this research analyse Islamic hotel room so as to have a deep understanding of facilities and services, its elements and requirements. The main objective is to establish the for Muslim Friendly Hotel room audit checklist and guidelines. Interview, observation and focus group discussion were used and triangulate for validation in qualitative research. Analysis of data revealed that room in 8 non shariah compliant hotels observed required at least 12 twelve elements to become Muslim Friendly Hotel. Observation also established that for shariah compliant hotel at least ten elements fulfilled. Therefore, developing audit checklist for Muslim Friendly Hotel room has been identified as a key finding to standardize the elements in-room facilities and services in all Muslim Friendly Tourism Accommodation Premises to facilitate Muslim Tourist.